A Review of Routing Algorithms and their extensions for Optical Networks: Advancements and Future Directions in Optical Routing Algorithms (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The execution of an interconnection network is profoundly affected by specific properties ofthe directing calculation which are being utilized. This paper manages the investigation of the directingcalculations proposed and survivability in writing for optical systems. This paper gives the concisewriting survey on the point what's more, finished up with a portion of the work which should be possiblein this zone. Aim is to get a review of the work done on various optical routing algorithms to get an ideaof the work and then to get further extensions. Wavelength Division Multiplexing (WDM) is as of now areality for optical transmission frameworks with numerous sellers offering arrangements andmodifications.